2017
DOI: 10.1007/978-3-319-58515-4_24
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and Matching Learning Design and Learning Analytics

Abstract: Abstract. In the last five years, learning analytics has proved its potential in predicting academic performance based on trace data of learning activities. However, the role of pedagogical context in learning analytics has not been fully understood. To date, it has been difficult to quantify learning in a way that can be measured and compared. By coding the design of e-learning courses, this study demonstrates how learning design is being implemented on a large scale at the Open University UK, and how learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(69 reference statements)
2
16
0
Order By: Relevance
“…When it comes to learning design activities (see Appendix C), most of the studies included in the review have used assimilative, assessment, communication, finding and handling of information, and productive activities, as defined in the learning design taxonomy [34]. This is also supported by Rienties and Nguyen research studies on the impact of learning design in university settings [5], [46], [86], [85]. They reported that learning design has a strong influence on learner's satisfaction [5].…”
Section: B Interpretation Of the Results With Respect To The Second mentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to learning design activities (see Appendix C), most of the studies included in the review have used assimilative, assessment, communication, finding and handling of information, and productive activities, as defined in the learning design taxonomy [34]. This is also supported by Rienties and Nguyen research studies on the impact of learning design in university settings [5], [46], [86], [85]. They reported that learning design has a strong influence on learner's satisfaction [5].…”
Section: B Interpretation Of the Results With Respect To The Second mentioning
confidence: 99%
“…In particular, communication and interactive activities engage students to spend more time in VLEs compared to productive and experiential activities [86]. Although the design of learning activities depend on the module [85], educators design learning activities differently over the time line of the course and reduce the variety of learning design activities when they introduce assessment activities [46].…”
Section: B Interpretation Of the Results With Respect To The Second mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, by capturing and visualizing the design of learning activities, the LD approach could provide a pedagogical context to support interpreting and translating LA findings into interventions (Lockyer et al, 2013;Persico & Pozzi, 2015). A gradual accumulation of empirical evidence has indicated great potential in connecting LA with LD (Gašević, Dawson, Rogers, & Gasevic, 2016;Nguyen, Rienties, & Toetenel, 2017a;Nguyen, Rienties et al, 2017b;Nguyen, Rienties, Toetenel, Ferguson, & Whitelock, 2017;Rienties & Toetenel, 2016;Rienties et al, 2015). In a large-scale study of 151 modules and their 111,256 students at a distance educational institution, for example, Rienties and Toetenel (2016) revealed significant relations between LD and VLE behaviour, along with student satisfaction and retention.…”
Section: Learning Designmentioning
confidence: 99%
“…Although it is not related to collaborative classes, Nguyen, Rienties, and Toetenel (2017) provide an example of analyzing learning activities based on learning designs. They illustrate the variance in the time allotted for different activities over 32 course weeks in 24 modules of the Open University, UK (Nguyen et al, 2017). They start by categorizing learning activities into six types (e.g., assimilative: paying attention to information) with reference to Rienties and Toetenel (2016).…”
Section: Relationship Between Teachers and Contentmentioning
confidence: 99%